Women and the Rise of Nutrition Science in Interwar Britain and British Africa - Sparks, Lacey. author. aut Link
VIII, 206 p. 1 illus.
Keywords: In the wake of the Great Depression, economic recovery and nutritional improvement in Britain simultaneously occurred with their decline in British Africa. While histories of science, medicine and British Empire have provided fertile analytical ground for decades, the field of nutrition science has received comparatively little attention. Widespread malnutrition between the World Wars called into question the role of the British state in preserving the welfare of both its citizens and its subjects, especially women, given their role in feeding their families. International organizations such as the League of Nations, empire- wide projects such as nutrition surveys conducted by the Committee for Nutrition in the Colonial Empire (CNCE), sub-imperial networks of medical and teaching professionals, and individuals on-the-spot wove a dense web of ideas on nutrition. Women, especially of the working class, bore the brunt of the struggle to access nutritious food as a wave of interestin the new science of nutrition swept the globe between the wars, with imperial Britain in the lead. The British state buoyed the economic slump of the Great Depression in the metropole by importing more colonial goods more cheaply, feeding metropolitan Brits on the back of the colonial empire, particularly in Africa. This book stands apart for the way it places nutrition science in both Britain and Africa under a single analytic lens of economics, gender and empire, contributing to research on British and African history, British Empire, women’s history and the history of science, medicine and health. Lacey Sparks is an Assistant Professor of Modern European History at the University of Southern Maine, in the USA. Her research focuses on Britain and the empire, gender, and the cultural history of food, science, and medicine. She is particularly interested in the multiple and multidirectional exchanges— political, economic, and cultural—that comprised and subverted theEmpire. She also teaches World History, History of the British Empire, Women’s History, and History of Africa.